Colostrum avoidance and associated factors among postnatal mothers in health facilities in Addis Ababa, Ethiopia: a mixed method study - Belete Mengistu Sisay; Samson Zegeye Endale; Frehiwot Worku Senbeta (BMC Public Health)
Abstract Background Colostrum is the first form of milk produced immediately following the delivery of a newborn. It is highly nutritious and contains antibodies to protect the newborn against disease and crucial for the newborn’s health Despite its benefits, some mothers avoid giving colostrum to their newborns. Objective This study aims to assess the prevalence and factors associated with colostrum avoidance among postnatal mothers in Addis Ababa, Ethiopia. Methods A health facility-based mixed-methods of study design was conducted. Both quantitative and qualitative data were collected using pretested questionnaires and key informant interview question guides, respectively.Quantitative data were collected through structured interviews and analyzed using descriptive statistics such as frequencies, means, and standard deviations were performed. Binary logistic regression analysis was employed to assess the associated factors of colostrum avoidance among postnatal mothers at health facilities in study area.Qualitative data were gathered via in-depth interviews and analyzed thematically. Results The prevalence of colostrum avoidance was 8.94% (95% CI: 5.9–10.9). Multivariable analysis revealed significant predictors of colostrum avoidance: lack of counseling about colostrum benefits (AOR = 5.802, 95% CI: 2.467–13.647), cesarean delivery (AOR = 3.420, 95% CI: 1.411–8.288), poor maternal knowledge about colostrum (AOR = 13.111, 95% CI: 5.462–31.468), and late initiation of breastfeeding (AOR = 3.330, 95% CI: 1.242–8.926). Qualitative findings echoed these results, with cultural beliefs and misconceptions about colostrum contributing to its avoidance. Conclusion The study highlights a significant prevalence of colostrum avoidance among postnatal mothers in Addis Ababa. Key predictors include inadequate counseling, cesarean delivery, poor knowledge about colostrum, and delayed breastfeeding initiation. Interventions aimed at improving maternal education and breastfeeding practices are essential to reduce colostrum avoidance.